2001
DOI: 10.1088/0953-4075/34/9/316
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the neon 2p collisional excitation transfer processes via CW laser collisionally induced fluorescence

Abstract: We present a method for determining the 2p (in Paschen notation) collisional excitation transfer coefficients in noble gases using continuous-wave laser collisionally induced fluorescence (CW LCIF, i.e. fluorescence from an upper level which is not that of the laser transition). The technique requires isolation of the specific 2p coupling process under examination, whereby that process provides an important and quantifiable contribution to the LCIF. This is achieved by selecting appropriate laser excitation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 18 publications
2
10
0
Order By: Relevance
“…Analysis of several emission lines and populations (from absorption spectroscopy) provides a range of information and enhances the reliability of the determination. We have combined these widely used optical diagnostic techniques with related methods [9][10][11][12] which provide extensive information on the kinetics between the excited states, allowing sampling of the EDF across a wide range of electron energies.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of several emission lines and populations (from absorption spectroscopy) provides a range of information and enhances the reliability of the determination. We have combined these widely used optical diagnostic techniques with related methods [9][10][11][12] which provide extensive information on the kinetics between the excited states, allowing sampling of the EDF across a wide range of electron energies.…”
Section: Introductionmentioning
confidence: 99%
“…The partial differentials are obtained using the expression for I jJ , the intensity of the 2p j -1s J transition, given in equation ( 4). The theoretical modelling and evaluation of all of these terms in equation ( 6) and their relative contributions are discussed in detail in our previous publications [6][7][8] for a number of different typical cases. Equation ( 6) may be solved to obtain the final expression [6]: where β jJ is the branching ratio from 2p j to 1s J , including collisional depletion routes and δ jJ is given by…”
Section: Cw Laser Collisionally Induced Fluorescencementioning
confidence: 99%
“…The results we report here constitute part of ongoing development and application of our complementary approach to optical diagnostics of low-temperature plasmas based on the excited-state kinetics of noble gas atoms in the metastable and resonance states. In previous studies [6][7][8][9][10] we used the well-behaved neon positive column plasma to demonstrate the diagnostic power of combining two steady-state techniques (optical emission and absorption spectroscopy (OES and OAS)) with two CW laser-perturbed steady-state techniques (the optogalvanic effect (OGE) and laser collisionally induced fluorescence (LCIF)). In this work we describe our models for the argon 1s populations, emission line ratios and the CW LCIF spectra observed for laser excitation out of the 1s 5 state.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore we consider collisions of Ne(2 p 5 3 p ) with He and Ne, where Penning ionization cannot occur. Ne(2 p 5 3 p ) + Ne collisions have been studied by several investigators. Chang and Setser found that the 3 p [1/2] 1 level is quenched (loss to levels outside of the 2 p 5 3 p manifold) with a rate constant of 1.7 × 10 –11 cm 3 s –1 , which is too fast for the proposed application. Collisions between Ne(2 p 5 3 p ) and He have also been examined, ,, but all of the state-to-state transfer measurements have focused on the higher energy levels (in part because the 632.8 nm line of the HeNe laser terminates on the 3 p ′[3/2] 2 level).…”
Section: Introductionmentioning
confidence: 99%